Hemosiderotic Fibrolipomatous Tumor on FDG PET/CT. (February 2019) - Yang, Fanhui; Chen, Fei; Cao, Lingzhi; Lin, Shiyu; Li, Suping
Abstract : Abstract: A 74-year-old woman with a history of melanoma 10 years ago presented worsening swelling pain associated with a lump in her inner left thigh. Metastatic disease was suspected and for this reason, FDG PET/CT was performed. The images demonstrated peripherally increased FDG activity in the lump with a centrally photopenic region. Postsurgical pathological examination showed a hemosiderotic fibrolipomatous tumor.